Carbonated beverage consumption of young adults in Singapore - Cai, Tingting (2008)
Carbonated drinks have been really popular; however sales have started to slow down. Although there has been much controversy about how unhealthy carbonated drinks are and after all the 'healthy living' campaigns by the government in different countries, carbonated drinks still rank as the No. 1 selling soft drink in the market. There has been past research attempts on consumption of beverages, however none has focused on carbonated drinks alone. Hence, this project attempts to investigate the consumption of carbonated drinks among young adults while focusing on Singapore.